2009
DOI: 10.4315/0362-028x-72.7.1538
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli O157:H7 and Natural Microbiota on Spinach Leaves Using Gaseous Ozone during Vacuum Cooling and Simulated Transportation

Abstract: The aim of this study was to integrate an ozone-based sanitization step into existing processing practices for fresh produce and to evaluate the efficacy of this step against Escherichia coli O157:H7. Baby spinach inoculated with E. coli O157:H7 (approximately 10(7) CFU/g) was treated in a pilot-scale system with combinations of vacuum cooling and sanitizing levels of ozone gas (SanVac). The contribution of process variables (ozone concentration, pressure, and treatment time) to lethality was investigated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 25 publications
3
28
0
1
Order By: Relevance
“…Vurma, Pandit, Sastry, and Yousef (2009) found that ozone at 935 ppm for 30 min inactivated 1.8 log CFU/g of E. coli O157:H7 with no apparent loss of quality In a separate set of experiments, they treated refrigerated spinach with low ozone levels (5 to 10 ppm) for up to 3 days and decreased E. coli populations by up to 1.4 log CFU/g with minimal effect on product quality (Vurma et al, 2009). Spinach samples exposed to ClO 2 gas for two different treatment times (30 min and 1 h) did not reduce the respective pathogen populations beyond the control water wash. Rodgers et al (2004) reported that ozone reduced E. coli O157:H7 counts on multiple types of produce by more than 5 log CFU/g.…”
Section: Effects Of Sanitizers On E Coli O157:h7mentioning
confidence: 99%
“…Vurma, Pandit, Sastry, and Yousef (2009) found that ozone at 935 ppm for 30 min inactivated 1.8 log CFU/g of E. coli O157:H7 with no apparent loss of quality In a separate set of experiments, they treated refrigerated spinach with low ozone levels (5 to 10 ppm) for up to 3 days and decreased E. coli populations by up to 1.4 log CFU/g with minimal effect on product quality (Vurma et al, 2009). Spinach samples exposed to ClO 2 gas for two different treatment times (30 min and 1 h) did not reduce the respective pathogen populations beyond the control water wash. Rodgers et al (2004) reported that ozone reduced E. coli O157:H7 counts on multiple types of produce by more than 5 log CFU/g.…”
Section: Effects Of Sanitizers On E Coli O157:h7mentioning
confidence: 99%
“…Many treatments have been proposed for the decon tamination of fresh produce, including single or combined application of chemical sanitizers, detergents, organic acids, UV light, ozonation, pulsed UV light, high pressure, ionizing irradiation, and several other treatment methods (4,29,30,38,40,41). Currently, chlorinated and nonchlorinated chemical treatments are the most common disinfection methods used in produce processing plants.…”
mentioning
confidence: 99%
“…E. coli O157:H7 has been a constant concern to the food industry. Various antimicrobial sprays and treatment methods have been employed with partial success to actively reduce the bacterial contamination from beef carcasses and food products (9,25,26,30,45,47,55,59). This study observed that three vital cellular processes, cell division, biofilm formation, and pathogenicity, were all downregulated by FlhC.…”
Section: Discussionmentioning
confidence: 99%